The impact of fintech adoption on small and medium enterprises in Malaysia - Faizal, Diana Rose; Hasim, Rati (Research and Scientific Innovation Society, 2025)
The rapid advancement of Financial Technology (FinTech) has reshaped global industries by integrating digital tools such as e-wallets, mobile banking, artificial intelligence, and blockchain into financial services. In Malaysia, the SMEs has increasingly adopted these technologies to enhance operational efficiency, improve customer experience, and support digital transformation. Despite this growth, small and medium-sized enterprises (SMEs) continue to face challenges in fully realizing the financial benefits of FinTech adoption due to barriers such as cybersecurity risks, limited infrastructure, regulatory compliance, and difficulties in measuring return on investment (ROI). This study investigates the factors influencing FinTech adoption among retail business owners in Malaysia and examines its impact on financial performance. Guided by the Unified Theory of Acceptance and Use of Technology (UTAUT) model, a quantitative research design was employed using a structured questionnaire distributed to retail business owners familiar with FinTech applications. A purposive sampling method was adopted with a target of 384 respondents, and data will be analyze using SPSS. The findings are expected to provide empirical evidence on the relationship between FinTech adoption and business performance, particularly in the context of SMEs. The study contributes to academic literature on technology adoption and offers practical insights for policymakers, regulators, and retail entrepreneurs in enhancing digital financial integration. By addressing gaps in existing research, this work underscores the role of FinTech in supporting competitiveness, sustainability, and inclusive growth in Malaysia’s retail industry.